2020
DOI: 10.1002/ppap.202000086
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical surface analysis and germination at different irrigation conditions of DBD plasma‐treated wheat seeds

Abstract: Plasma treatment is increasingly being explored as an effective presowing treatment improving seed germination. This study examines the synergetic effect of the irrigation condition and the physicochemical surface properties of wheat seeds subjected to atmospheric dielectric barrier discharge plasma activation on their water uptake and germination. Extensive surface analysis revealed a remarkably enhanced wettability of plasma‐treated seeds due to the insertion of oxygen‐containing functionalities on their sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 54 publications
7
44
0
Order By: Relevance
“…[ 34,58,63–66 ] Direct plasma treatment is changing the WCA and seed hydrophilicity to a great degree, originate from the incorporation of oxidized functional groups on the seed surface [ 61 ] and often leading to accelerated germination. [ 34,67–69 ] Our study, on the contrary, indicated that surface hydrophilicity of barley, rape, and lupine seeds were not changed by PPA treatment as concluded from the unchanged WCAs for each plant species. This different impact of direct and indirect plasma treatment on WCA has been noted before.…”
Section: Discussionmentioning
confidence: 53%
“…[ 34,58,63–66 ] Direct plasma treatment is changing the WCA and seed hydrophilicity to a great degree, originate from the incorporation of oxidized functional groups on the seed surface [ 61 ] and often leading to accelerated germination. [ 34,67–69 ] Our study, on the contrary, indicated that surface hydrophilicity of barley, rape, and lupine seeds were not changed by PPA treatment as concluded from the unchanged WCAs for each plant species. This different impact of direct and indirect plasma treatment on WCA has been noted before.…”
Section: Discussionmentioning
confidence: 53%
“…However, adhesive tape was used to hold the seeds during the plasma treatment which may or may not have affected the results. This inconsistency in seed coat erosion may be partly due to the seed type as described by Molina et al (2020), who noticed that nasturtium seeds were less prone to etching than wheat seeds under the same experimental conditions (Molina et al, 2018). SEM can also be used to observe surface roughness where Pawłat et al (2018) interpreted the more creased appearance with an increase in micro-roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Using cartography images, Gómez-Ramírez et al (2017), and Molina et al (2018, observed a migration of potassium from the interior to the exterior in cross-sections of quinoa, nasturtium and wheat seeds after dry air plasma, and helium plasma treatment, respectively. Molina et al (2020) explained the initial movement of potassium as being due to the polar-containing groups on the seed coat. Gómez-Ramírez et al (2017) pointed out that, with the addition of water vapor, the potassium and nitrogen-containing groups decreased, presumably because they were absorbed by the seed and thereby improving seed germination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key subtopic, LTPs in the treatment of seeds and plants, is addressed in five articles, specifically as it applies to wheat, [ 9 ] Norway spruce, [ 10 ] red clover, [ 11 ] rice, [ 12 ] and maize and barley. [ 13 ]…”
mentioning
confidence: 99%